The CORRELATION BETWEEN HUSBAND SUPPORT WITH ADJUSTMENT IN MOTHER OF CHILDREN WITH AUTISM DISORDER - Merita Naisanu; Triana Noor Edwina Dewayani Soeharto (Institut Agama Kristen Negeri Kupang, 2021)
This research is aimed to find out the correlation between husband support with adjustment in mother of children with autism disorder. Hypothesis of the research are : There is a positive correlations between support husband with adjustment in mother of children with autism disorder. The tool for gathering data using the scale of husband support, and the scale of adjustment. The subjects of this research were 37 mothers of children with autism disorder in “ Yayasan Permata Ananda Yogyakarta and “SLB Negeri Pembina Kupang”. To analise the data research uses : test of assumption, and test of hypothesis with product moment correlation The research results showed there is a positive correlation between husband support and adjustment in mother of children with autism disorder, with correlations coefficients score 0,008, (p<0,01). There is correlation between husband support with adjustment in mother of children with autism with R square 0,329 or 32,9 % , which means that 32,9% of adjusment in mother of children with autism disorder variable is explained by husband support and the rest of 67,1% is explained by another variable.